2020
DOI: 10.1111/cas.14517
|View full text |Cite
|
Sign up to set email alerts
|

MiR‐145 in cancer therapy resistance and sensitivity: A comprehensive review

Abstract: MircoRNA (miRNA) are a group of small, non–coding, regulatory RNA with an average length of approximately 22 nucleotides, which mostly modulate gene expression post–transcriptionally through complementary binding to the 3ʹ‐untranslated region (3ʹ‐UTR) of multiple target genes. Emerging evidence has shown that miRNA are frequently dysregulated in a variety of human malignancies. Among them, microRNA‐145 (miR‐145) has been increasingly identified as a critical suppressor of carcinogenesis and therapeutic resista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 83 publications
(102 reference statements)
2
28
1
Order By: Relevance
“…For instance, upregulation of miR-155 has been shown to be involved in chemotherapy resistance in several different cancers [ 117 ], while for miR-34 its low expression is associated with poor treatment response [ 118 ]. For both miRs, and several other prominent ones, their involvement in therapy resistance has been reviewed extensively by others [ 117 , 118 , 119 , 120 , 121 , 122 ]. However, the knowledge about miR involvement in chemotherapy resistance can be exploited to determine the efficiency of therapy strategies.…”
Section: Combination With Cancer Therapy To Counteract Mir-mediatementioning
confidence: 99%
See 1 more Smart Citation
“…For instance, upregulation of miR-155 has been shown to be involved in chemotherapy resistance in several different cancers [ 117 ], while for miR-34 its low expression is associated with poor treatment response [ 118 ]. For both miRs, and several other prominent ones, their involvement in therapy resistance has been reviewed extensively by others [ 117 , 118 , 119 , 120 , 121 , 122 ]. However, the knowledge about miR involvement in chemotherapy resistance can be exploited to determine the efficiency of therapy strategies.…”
Section: Combination With Cancer Therapy To Counteract Mir-mediatementioning
confidence: 99%
“…Once patients developed chemotherapy resistance, a promising approach to overcome chemotherapy resistance is the combined delivery of chemotherapeutics and miRs to sensitize tumor cells to chemotherapy, e.g., by targeting of DNA-damage response or cell cycle genes as well as genes related to apoptosis or multidrug resistance by co-delivered miRs [ 120 , 128 ]. However, in this review, we focus on the involvement of TME-derived or induced miRs in immune evasion and therapy resistance as well as on therapeutic candidates that deliver miRs and chemotherapeutics combined in nanoparticles to exploit their synergistic effect.…”
Section: Combination With Cancer Therapy To Counteract Mir-mediatementioning
confidence: 99%
“…The inhibition of the PI3K/AKT signaling pathway, which in turn induces MRP1 and P-gp inhibition, increases the sensitivity of esophageal squamous cell carcinoma to cisplatin and that of CRC to oxaliplatin. An increase in tumor cell sensitivity to the cytotoxic action of cetuximab in CRC was also observed, through a reduction of BCL2 and an increase in the activity of caspases 3/7 [48].…”
Section: Mir-145mentioning
confidence: 89%
“…The upregulation of mir-145 in obese mice prevents insulin-stimulated AKT activation [41]. The overexpression of mir-145 in CRC leads to the inhibition of the PI3K/AKT signaling pathway, which in turn increases the sensitivity CRC to oxaliplatin [48] A recent multi-omics approach and computational analysis on human visceral adipocytes compared the dysregulated miRNAs in obese subjects with or without CRC with normal weight controls [49]. MiR-193b-3p, miR-125a-5p, and miR-1247-5p, were found to be downregulated in both cancer and obese conditions.…”
Section: Pi3k/akt-common Pathway In Mets and Cancermentioning
confidence: 99%
“…Our results also showed that some miRNAs were expressed in both the AML and HD groups but were significantly downregulated in AML patients compared to HD, among which we found miR-145, 150, 204, 365 and 518b. MiR-145 has been increasingly identified as a critical suppressor of carcinogenesis and therapeutic resistance in several cancers [ 49 ]. Recent data showed that the level of this miRNA in serum and bone marrow mononuclear cells of AML patients was significantly lower than that of HD and was related to poor prognosis [ 50 ].…”
Section: Discussionmentioning
confidence: 99%